Ramadan Fasting Among Older Children and Adolescents With Type 1 Diabetes Mellitus: A Real-World Study From the UAE - Muammar, Tawfik; Fojas, Esphie Grace Fodra; Helal, Radwa; Lessan, Nader (Frontiers in Nutrition, 2022)
Background Ramadan fasting (RF) is a religious obligation for all healthy adult Muslims. The sick and pre-pubertal children are exempt, but many choose to fast for various reasons. In this “real world” study, we have investigated glycaemic control in the context of RF in children and adolescents with Type 1 diabetes (T1D) and compared multiple daily injections (MDI) and continuous subcutaneous insulin infusion (CSII) outcomes. Methods Children and adolescents with T1D seen at Imperial College London Diabetes Centre who decided to fast in the ensuing Ramadan were educated with their families about diabetes management during RF using an adapted CHOICE (Carbohydrate, Insulin, and Collaborative Education) educational programme. Pertinent data including hypoglycaemia episodes and diabetic ketoacidosis (DKA) were obtained through patient/family interviews. Information on weight, HbA1c, and blood glucose levels from continuous glucose monitoring(CGM)/flash glucose monitoring(FGM) before (one month prior), during, and after (one month afterwards) Ramadan were retrieved retrospectively from the electronic database. Data are presented as mean ± SD. Results 47 patients with T1D (age 13.40 ± 2.42 years; diabetes duration 4.6 ± 3.1 years; 29 (61.7%) males, 18 (38.3%) females; 26 (55%) on MDI, 21 (45%) on CSII) were included in the study. 42 (89%) were able to fast for 22.3 ± 8.7 days during Ramadan. No statistically significant differences were seen in CGM/FGM generated mean blood glucose level before, during, and after Ramadan [one-way ANOVA (F(2,80)=1.600, p=0.21)], as well as before and during [t(16)=-.960, p=0.35)], before and after [t(27)=.115, p=0.91)], and during and after [t(12)=1.493, p=0.16)] Ramadan. Post-Ramadan HbA1c and weight did not change significantly compared to baseline (paired t-test; p=0.02 and p=0.08, respectively). Between MDI and CSII, there was no significant difference in fasting days (p=0.49), frequency of hypoglycaemia episodes (p=0.98), DKA frequency (p=0.37), HbA1c level (p=0.24), and weight (p=0.11) after Ramadan. Conclusion Although RF for children and adolescents with T1D particularly those with poor glycaemic control involve high risks, patients do undertake RF due to religious or other reasons. Our data show no significant deterioration in indicators of overall glycaemic control which remained inadequate. RF should be discouraged in children with poorly controlled T1D.